STUDY OF THE INFLUENCE OF LORATADINE AND DESLORATADINE ON 15-LIPOXYGENASE ACTIVITY - СМІШКО, Р. О.; СТРАШНИЙ, В. В.; ЛІСОВИЙ, В. М.; ЛИЖНЮК, В. В.; ГОЙ, А. М.; САВЧЕНКО, К. І.; ВАХІТОВА, Л. М.; БЕССАРАБОВ, В. І. (Technologies and Engineering, 2023)
Purpose. Investigation of the effect of antihistamine active pharmaceutical ingredients (APIs) loratadine and desloratadine on the activity of 15-lipoxygenase in the reaction of enzymatic oxidation of linoleic acid as a substrate. Methodology. Study of kinetic patterns and mechanisms of 15-lipoxygenase inhibition using the spectrophotometric method. Calculation of kinetic parameters according to standard methods and kinetic models in the SigmaPlot 14.0 software package. Findings. The dependence of the stationary rate of substrate conversion by 15-lipoxygenase on substrate concentrations without an activator and in the presence of loratadine in different concentrations was investigated. It was established that loratadine dose-dependently accelerates the conversion of the substrate by the enzyme and, thus, exhibits potential pro-inflammatory properties (Ka=29.60 ±8.28 µM). It was shown that in the presence of desloratadine in concentrations of 25 μM, 50 μM, 100 μM in the 15-LOX linoleic acid oxidation system, a decrease in the steady-state rate of substrate conversion by the enzyme is observed. At the same time, the concentration of half-maximal inhibition of fever is IC50=287.91 ± 29.02 µM. The mechanism of inhibition of 15-lipoxygenase by desloratadine was established, which corresponds to the Mixed (Partial) model of inhibition (R2=0.9688). Originality. For the first time, it was established that loratadine, unlike desloratadine, activates 15-lipoxygenase, which indicates its potential pro-inflammatory properties. Practical value. The conducted studies prove that desloratadine can potentially be used as an active pharmaceutical ingredient of drugs with anti-inflammatory properties, as it has a high efficiency as a 15-LOX inhibitor. The use of this API will avoid the phenomenon of polypharmacy and reduce the number of adverse reactions in the patient’s body that occur during traditional therapy with nonsteroidal anti-inflammatory drugs. It was concluded that in geriatric practice for the treatment of allergic diseases it is advisable to give preference to drugs based on desloratadine. Long-term use of loratadine in the elderly can provoke an increase in the inflammatory process and acceleration of oxidative stress.